Promise and Unrest - Grossman, Alan; O’Brien, Áine (Ireland, 2010)
Verzio FF submission Separated from her daughter Gracelle at 7 months, Noemi Barredo left the Philippines for work in Malaysia to support her parents and extended family before arriving in Ireland in 2000. Filmed over a five-year period "Promise and Unrest" is an intimate portrayal of a migrant woman performing caregiving and long-distance motherhood, while assuming the responsibility of sole provider for her family back in the Philippines. Dublin may be a long way from Noemi’s hometown of Babatngon, yet she retains a sharp eye on the welfare of her family, attentive to a range of small businesses she has financed, paying for the education of her daughter and son, medication for her terminally ill father and her sister’s nursing degree. The film captures the everyday intricacies of Noemi and Gracelle’s relationship, their reunion in Ireland and the beginnings of a domestic life together in the same country for the first time.